Cross-cultural Ambiance in Mohsin Hamid’s Novel Exit West - Bishnu Prasad Pokharel (Interdisciplinary Journal of Management and Social Sciences, 2024)
Hamid’s novel Exit West (2017) envisions the possibility of restructuring the identity, experience, and living conditions of individuals by providing opportunities for interconnectedness, community sharing, and compassionate human standing in a cross-cultural set-up. Based on the novel’s narrative, this paper highlights that individuals restricted within suffocating territorial boundaries try to escape through a magical door, as indicated in the novel, in search of a space where a multicultural milieu finds a congenial environment for living. Cross-cultural theory is the theoretical framework used to analyze the novel. Employing the qualitative technique, the paper analyzes the acclimatization process of a culturally and ethnically diverse society, including the socio-psychological behavior of people. This paper infers that when individuals confront terror and unrest in a country and culture, their escape to a new locale endows them with an unexpected welcome gesture and enhances their life and living, indicating what multicultural association can do to humanity. Ultimately, it deduces that the escape of the protagonists of the novel Saeed and Nadia from their hometown through a magic door to Greece and London before eventually settling in San Francisco for social security implies the significance of a multicultural locale. Despite their assorted upbringing, they develop compassionate feelings in the new location, internalizing the entire world as a global cultural village. The acceptance of a broader community, epitomizing the diverse spectrum of humanity, creates a milieu of harmony. This study acclaims cross-cultural assimilation for physical, psychological, and social well-being.